Ovarian tissue cryopreservation after graft failure of allogeneic hematopoietic stem cell transplantation: first report and literature review - Zhang, Jinghua; Li, Xiaowei; Liang, Rong; Duan, Shengnan; Yang, Xin; Hou, Yanru; Tian, Li (Frontiers in Endocrinology, 2024)
Background: Hematopoietic stem cell transplantation (HSCT) is an approach that has significantly improved the prognosis and survival of hematological patients. However, ovarian dysfunction and infertility following HSCT have gained increasing attention. Live births have been reported following ovarian tissue cryopreservation prior to HSCT and subsequent retransplantation of these tissues. Still, the feasibility of ovarian tissue cryopreservation (OTC) following graft failure (GF) of HSCT remains unknown. In this study, we report the first case of OTC following a GF of allogenic HSCT (allo-HSCT), as well as the cryopreservation of 4 MII oocytes via in vitro maturation with informed consent. Despite the lack of clinical outcomes after cryopreserved ovarian tissue retransplantation, we documented an interesting case in a female after GF of allo-HSCT exhibiting functional ovaries and emphasized a clinical dilemma: whether OTC should be offered to females suffering from GF of HSCT.Case presentation: A 22-year-old female with severe aplastic anemia who had suffered GF of allo-HSCT from her sibling brother [HLA allele match (7/10)] with a reduced dose conditioning regimen including fludarabine, cyclophosphamide, and antiothymocyte globulin came to our reproductive center for fertility preservation, as she was about to receive the second allo-HSCT. We evaluated the ovarian reserve of this patient. Hormone assessments showed an anti-Müllerian hormone level of 3.921 ng/mL, a follicle-stimulating hormone level of 5.88 IU/L, a luteinizing hormone level of 10.79 IU/L, and an estradiol level of 33.34 pg/mL. Antral follicle counts accessed transvaginally showed 12-15 follicles. All assessments indicated a well-protected ovarian reserve. Due to the urgency of the second allo-HSCT, the patient decided to undergo ovarian cryopreservation. Laparoscopic surgery proceeded. Ovarian tissues were successfully cryopreserved using vitrification technology, and histologic evaluation demonstrated a follicle density of 20 per 2 × 2 mm 2 biopsy with good viability. Four MII oocytes were obtained via in vitro maturation technology and cryopreserved. After the second HSCT, the patient relieved from aplastic anemia but suffered iatrogenic premature ovarian failure as predicted.OTC is applicable to fertility preservation in those undergoing GF of HSCT with benign hematological disorders and especially those who are about to receive the second HSCT.